Retenção do dimetoato e sua relação com pH e teores de argila e matéria orgânica nos sedimentos da zona não-saturada de uma microbacia no nordeste paraense - LIMA, Lilianne Maia (Instituto Nacional de Pesquisas da Amazônia, 2015)
On smallholder farms of eastern Amazonia, in particular the northeast of the Pará state, heavy by pesticide applications at industrial half-perennial crops are very common. Due to their large use, mainly the dimethoate, in the catchment of the Cumaru stream, Igarapé-Açu county, we evaluated the retention process of this compound in samples of the non saturated zone, as well as verified the effects of soil pH and clay and organic mater contents in this process. Among the main pesticides the farmers use in this region, dimethoate was selected for this study, due to its larger leaching potential according to the GUS (Groundwater Ubiquity Score) index. A sorption experiment was carried out to evaluate the retention of the dimethoate in sediments in the non saturated zone. The experiment showed that the sorption of the dimethoate varied from 2.5% to 36.2% (initial concentration of 20 mg.l-1) and from 6.2% to 31.0% (initial concentration of 10 mg.l-1). These data demonstrate a high contamination potential of the groundwater by this compound, mainly due to its high mobility and low retention capacity. The dimethoate sorption rates were positively related to organic matter content in the sediments. On the other hand, values have an inverse relationship with the sorption rates of dimethoate, while clay content did not produce any effect on its retention.